Limiting the Legality of Determining Suspects in Indonesia Pre-Trial System - Suarda, I Gede Widhiana; Taufiqurrohman, Moch. Marsa; Priambudi, Zaki (Indonesia Law Review, 2021)
This article aims to examine what the pre-trial judges consider in determining whether a suspect's determination is legal. The basis of the reason "not based on the provisions and legal procedures in force" is a pre-trial petition. Including examining whether the Notification Letter for the Commencement of Investigation has not been submitted to the Reported Party and the Reporting Party, it can be used as a basis for the judge's consideration to judge the legality of the determination of the suspect. This article uses a legal research method through a statutory, conceptual, and case approach. This article finds that after the issuance of the Constitutional Court Decision Number 21 / PUU-XII / 2014 and the Supreme Court Regulation Number 4 of 2016, the fulfillment of preliminary evidence, namely that two valid tools of evidence constitute the absolute standard of determining the suspect. Besides, in terms of proof, pre-trial only assesses the validity of formal aspects, which incidentally do not touch the case's subject matter. An application for the cancellation of a suspect's status, for whatever reason, cannot be granted if the initial evidence is not fulfilled, namely the two tools of evidence listed in Article 184 paragraph (1) of the Law of Criminal Procedure (KUHAP). Ultimately, this study recommends the need for affirmation in terms of determining suspects through changing the parameters for deciding suspects in Article 1 point 11 of the Draft of the Law of Criminal Procedure from what was originally only based on "...sufficient preliminary evidence" to "...the fulfillment of two tools of evidence contained in Article 175 paragraph (1) of the Law of Criminal Procedure" to achieve legal certainty and fulfill the suspect's human rights.